2000
DOI: 10.1080/00365510050184949
|View full text |Cite
|
Sign up to set email alerts
|

Impact of blood sampling in very preterm infants

Abstract: In a prospective investigation, 99 very preterm infants (gestational age (GA) 24 32 weeks, birthweight 560-2,255 g) were studied during the first 4 weeks of life. The infants were divided into two groups: infants born extremely early (GA <28 weeks, n = 20) and infants of GA 28 - 32 weeks; the groups were then subdivided into critically ill or not. Diagnostic blood sampling and blood transfusion events were recorded. In total, 1905 blood samples (5,253 analysis) were performed, corresponding to 0.7 samples (1.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 15 publications
2
40
0
2
Order By: Relevance
“…This is largely due to the complications in determining the erythropoiesis rate caused by frequent phlebotomies and RBC transfusions altering the RBC/Hb mass, and the effect of each phlebotomy on the RBC/Hb removal rate due to the life span-based disposition of RBCs (Landaw, 1988;Freise et al, 2007Freise et al, , 2008. Previous studies have demonstrated that on average 33.8 ml/kg blood is removed and 27.0 ml/kg blood is transfused during the first 4 weeks of life in infants born at a gestational age of less than 28 weeks (Madsen et al, 2000), and other studies have reported even higher phlebotomy blood loss volumes in the first 2 weeks of life alone (Lin et al, 2000;Widness et al, 2005). Thus, the effects of the physical removal and administration of RBCs are substantial and cannot be ignored.…”
mentioning
confidence: 99%
“…This is largely due to the complications in determining the erythropoiesis rate caused by frequent phlebotomies and RBC transfusions altering the RBC/Hb mass, and the effect of each phlebotomy on the RBC/Hb removal rate due to the life span-based disposition of RBCs (Landaw, 1988;Freise et al, 2007Freise et al, , 2008. Previous studies have demonstrated that on average 33.8 ml/kg blood is removed and 27.0 ml/kg blood is transfused during the first 4 weeks of life in infants born at a gestational age of less than 28 weeks (Madsen et al, 2000), and other studies have reported even higher phlebotomy blood loss volumes in the first 2 weeks of life alone (Lin et al, 2000;Widness et al, 2005). Thus, the effects of the physical removal and administration of RBCs are substantial and cannot be ignored.…”
mentioning
confidence: 99%
“…The first was a study from a developed country in which 99 very premature neonates (gestational age 24-32 weeks) had an average of 13.6 ml/kg of blood (equivalent to around 13% of TBV) drawn for testing during the first month after birth, and 19% of the 99 neonates received at least one blood transfusion. 12 This study did not quantify the impact of blood sampling on Hb levels and did not attempt to separate the impact of blood loss through sampling from the effect of neonatal illness, but the findings do suggest that this level of sampling was often associated with the need for transfusion, which takes it out of the minimal risk category. This conclusion is consistent with the findings of a similar Stephen RC Howie Safe blood sample volume limits in children…”
Section: Empirical Evidencementioning
confidence: 95%
“…Measurement of TSB concentrations is a frequent reason for collection of blood from newborns, especially preterm infants (18 ). For newborns, the majority of the samples are taken by heelstick, which can be painful and involves other potential complications of blood collection, including infection and possibly osteomyelitis (19 ).…”
Section: Tcb and Clinical Outcomementioning
confidence: 99%